2021
DOI: 10.1007/s00330-021-07714-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrast agent dose reduction in computed tomography with deep learning using a conditional generative adversarial network

Abstract: Objectives To reduce the dose of intravenous iodine-based contrast media (ICM) in CT through virtual contrast-enhanced images using generative adversarial networks. Methods Dual-energy CTs in the arterial phase of 85 patients were randomly split into an 80/20 train/test collective. Four different generative adversarial networks (GANs) based on image pairs, which comprised one image with virtually reduced ICM and the original full ICM CT slice, were trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…In this context, it was shown that pathologies in artificially inhomogeneous collectives could be inserted or removed by GANs 25 . To avoid this, close monitoring of the training collective was ensured by pairing and coregistering the animals with themselves and checking pathological consistency, as described in our preliminary work 14 . In context of the present study pathological consistency means that no structure has been added or removed, all vessels are contrasted as expected, and no pathology has been added.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it was shown that pathologies in artificially inhomogeneous collectives could be inserted or removed by GANs 25 . To avoid this, close monitoring of the training collective was ensured by pairing and coregistering the animals with themselves and checking pathological consistency, as described in our preliminary work 14 . In context of the present study pathological consistency means that no structure has been added or removed, all vessels are contrasted as expected, and no pathology has been added.…”
Section: Discussionmentioning
confidence: 99%
“…14 Here, networks are trained to perform an image-to-image conversion from a low contrast dose images to a normal contrast dose images to reduce the required amount of contrast media by 50% to 80%. 14 So far, this method could only be evaluated for CT on virtual contrast-reduced images, based on a combination of dual-energy derived virtual noncontrast and iodine images. However, with these, it is uncertain whether contrast information remains in the image that the network can use for contrast enhancement.…”
mentioning
confidence: 99%
“…Also, generative networks, including additional types of architectures (e.g., autoencoders [AEs] and variational autoencoders [VAEs]), have the capability of improving the acquisition of multimodality imaging, such as MRI and CT scans, reducting radiation dose and use of intravenous contrast [ 29–31 ]. Since oncology patients must do routine scans for tumor staging, AE and VAE have the potential to reduce healthcare costs while improving patient safety.…”
Section: Artificial Intelligence For Cancer Imagingmentioning
confidence: 99%
“…Conditional GANs offer the possibility to generate one modality from another, alleviating the need to actually perform the potentially more harmful screenings-i.e. high-dose CT, PET-that expose patients to radiation, or require invasive contrast agents such as intravenous iodine-based contrast media (ICM) in CT [102], gadolinium-based contrast agents in MRI [103](in Table 5) or radioactive tracers in PET [104,105]. Furthermore, extending the acquisition modalities used in a given task would also enhance the performance and generalisability of AI models, allowing them to learn shared representations among these imaging modalities [24,106].…”
Section: Cross-modal Data Generationmentioning
confidence: 99%